Improving Chinese patients’ autonomy in medical decision-making through policy frameworks - Zhai, Gaoyuan (Frontiers in Public Health, 2025)
As rational organisms, human beings not only require a dignified existence in social relationships, but also require the ability to create themselves according to their own will and determine the development trajectory of their own lives. Medical decisions involve the patient’s life, health, body and other factors that are most closely related to the person. Individuals with dignity should make their own medical decisions and decide according to their own wishes. In Chinese society, due to the profound influence of Confucianism, medical familism occupies an important position in the doctor-patient relationship. Under the medical familism model, medical decisions are not the patient’s own private issues, but important matters that affect the future development of the entire family. When family members offer advice on medical decisions, in a positive sense they contribute overall wisdom to the patient’s medical treatment; however, in a negative sense, this may be seen as compressing the patient’s autonomy. In contemporary Chinese society, medical disputes occur frequently, and the harmonious doctor-patient relationship appears cracked. Improper exercise of medical decision-making is an important cause of many medical disputes. This article adopted the research methods of case analysis and comparative analysis. By analyzing the shortcomings of China’s current policy framework on medical decision-making and combining the influence of traditional Confucianism on China’s medical decision-making model, it proposed methods to improve China’s policy framework in order to enhance patients’ autonomy in medical decision-making.